Clinical and ultrasonographic features of medullary thyroid microcarcinomas compared with papillary thyroid microcarcinomas: a retrospective analysis - Li, Xiaoyu (BMC Med Imaging, 2020)
BACKGROUND: To identify the sonographic features that help to differentiate medullary thyroid microcarcinomas (MTMCs) from papillary thyroid microcarcinomas (PTMCs). METHODS: A total of 46 MTMCs in 41 patients and 136 PTMCs in 104 patients that were proven by surgery and pathology were included in the study. Patient age and nodule size were analyzed by independent sample t-tests, and sex, multiplicity and cervical lymph node metastases were analyzed by χ(2) or Fisher’s exact tests. Univariate analysis and multivariate logistic regression analysis were performed on the sonographic features of thyroid nodules, including location, shape, boundary, margin, peripheral halo ring, echogenicity, composition, calcifications and vascularization. RESULTS: Compared with the corresponding number of patients with PTMCs, more MTMC patients had cervical lymph node metastases (P = 0.040). There were no significant differences in age, sex, nodule size, multiplicity, location, boundary, margin, peripheral halo ring, echogenicity or microcalcifications between MTMCs and PTMCs (P > 0.05 for all). However, significant differences were found in shape (P = 0.000), composition (P = 0.032), macrocalcifications (P = 0.004) and vascularity (P = 0.000) between the two groups. CONCLUSIONS: There were some overlapping sonographic features between MTMCs and PTMCs. However, MTMCs tended to have a > 50% solid composition, be ovoid to round nodules with macrocalcifications and be hypervascular. Cervical lymph node metastases were more common in MTMC patients.